1983
DOI: 10.1002/cne.902210406
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of serotonin in the CNS of an elasmobranch fish: Immunocytochemical and biochemical studies in the atlantic stingray, Dasyatis sabina

Abstract: The distribution of serotonin (5HT) in the brain of the Atlantic stingray was studied with peroxidase-antiperoxidase immunocytochemistry and high-pressure liquid chromatography. The regional concentrations of 5HT determined for this stingray fell within the range of values previously reported for fishes. A consistent trend in vertebrates for the hypothalamus and midbrain to have the highest concentrations and the cerebellum the lowest was confirmed in stingrays. Neuronal cell bodies and processes exhibiting 5H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 56 publications
9
29
0
Order By: Relevance
“…No 5-HT-ir cells were observed in the SV of either developing or adult sharks. As reported in the batoid Dasyatis sabina [Ritchie et al, 1983], a few 5-HT-ir fibers innervated the shark SV, suggesting that they are saccopetal, probably arising from serotoninergic cells of the posterior recess nucleus.…”
Section: The Monoaminergic Systems Of the Shark Svsupporting
confidence: 56%
“…No 5-HT-ir cells were observed in the SV of either developing or adult sharks. As reported in the batoid Dasyatis sabina [Ritchie et al, 1983], a few 5-HT-ir fibers innervated the shark SV, suggesting that they are saccopetal, probably arising from serotoninergic cells of the posterior recess nucleus.…”
Section: The Monoaminergic Systems Of the Shark Svsupporting
confidence: 56%
“…This absence of 5-HT-ir cells and presence of extensive serotonergic innervation in the olfactory bulbs and pallial/subpallial telencephalic areas seems to be a shared feature across vertebrates, with the exception of chondrosteans, which showed immunoreactive cells in the olfactory bulbs and in the medioventral wall of the telencephalic ventricle, rostral to the anterior commissure [Adrio et al, 1999], and the marine teleost Micropogonias undulatus that possesses 5-HT-ir cells in the olfactory bulbs [Khan and Thomas, 1993]. Summary of the distribution of 5-HT-ir cells and fibers in different areas of the CNS of the main vertebrate groups studied 2 Ritchie et al [1983Ritchie et al [ , 1984, Cruce [1991, 1992], Stuesse et al [1990Stuesse et al [ , 1991aStuesse et al [ , b, 1995, Schuette and Chappel [1998], Carrera et al [2008].…”
Section: Forebrainmentioning
confidence: 99%
“…In mammals, 5-HT-containing intraspinal neurons were detected following pharmacological pretreatment to increase the level of 5-HT expression (Lamotte et al, 1982), whereas other studies have reported that serotonergic innervation is derived only from supraspinal structures (Kojima and Sano, 1983). It has thus been proposed that spinal cord 5-HT-ir cells were present early in phylogeny and have subsequently been lost in a number of species (Ritchie et al, 1983).…”
Section: Physiological Effect Of 5-htmentioning
confidence: 99%